Consensus Statement of the Italian Polispecialistic Society of Young Surgeons (SPIGC): Diagnosis and Treatment of Acute Appendicitis. Issue 10 (17th September 2021) - Guaitoli, Eleonora; Gallo, Gaetano; Cardone, Eleonora; Conti, Luigi; Famularo, Simone; Formisano, Giampaolo; Galli, Federica; Giuliani, Giuseppe; Martino, Antonio; Pasculli, Alessandro; Patini, Romeo; Soriero, Domenico; et al.
Abstract: Background: Acute appendicitis (AA) is one of the most common causes of abdominal pain requiring surgical intervention. Approximately 20% of AA cases are characterized by complications such as gangrene, abscesses, perforation, or diffuse peritonitis, which increase patients' morbidity and mortality. Diagnosis of AA can be difficult, and evaluation of clinical signs, laboratory index and imaging should be part of the management of patients with suspicion of AA. Methods: This consensus statement was written in relation to the most recent evidence for diagnosis and treatment of AA, performing a literature review on the most largely adopted scientific sources. The members of the SPIGC (Italian Polispecialistic Society of Young Surgeons) worked jointly to draft it. The recommendations were defined and graded based on the current levels of evidence and in accordance with the criteria adopted by the American College of Chest Physicians (CHEST) for the strength of the recommendations. Results: Fever and migratory pain tend to be present in patients with suspicion of AA. Laboratory and radiological examinations are commonly employed in the clinical practice, but today also scoring systems based on clinical signs and laboratory data have slowly been adopted for diagnostic purpose. The clinical presentation of AA in children, pregnant and elderly patients can be unusual, leading to more difficult and delayed diagnosis. Surgery is the best option in case of complicated AA, whereas it is not mandatory in case of uncomplicated AA. Laparoscopic surgical treatment is feasible and recommended. Postoperative antibiotic treatment is recommended only in patients with complicated AA.